Human field of regard, field of view, and attention bias. Issue 135 (October 2016) - Jang, Woncheol; Shin, Joon-Ho; Kim, Mingyu; Kim, Kwanguk (Kenny)
Highlights: A novel method for assessment and rehabilitation of human field of regard (FOR) and field of view (FOV) is proposed. We found a unique characteristic in the human FOR: The target responses were faster for the left side than the right side. This work is an important foundation for people who have FOR handicaps and future 3D UI design. Abstract: Background and objective: Human field of regard (FOR) is an important concept that should be considered along with field of view (FOV) for people with/without handicaps, but previous studies have neglected this aspect of human perception. In the current study, we suggest and test a new virtual reality (VR) software with which to evaluate individual's detection abilities in the human FOR. Methods: We conducted measurements of human FOV, FOR, and FOR with visual cue (FOR-cue), and we evaluated healthy adults' responses in a first experiment. Participants were asked to detect targets on a head-mounted display (HMD) as quickly as possible in three conditions: (a) FOV: the head rotation doesn't change the view of the screen in the HMD; (b) FOR: the head rotation changes the view of the screen in the HMD; and (c) FOR-cue: same with the FOR condition but an endogenous visual cue indicating the direction of stimulus. To address the need to increase the number of trials in the FOR condition, we also conducted a second experiment with new samples and four times of trial numbers. Results: The participants' detection time results indicated that the FOV condition was faster than the FOR-cue and FOR conditions, and the FOR-cue was faster than the FOR condition. Interestingly, we found a unique characteristic in the FOR conditions that did not exist in the FOV condition: The target responses were faster for the left side than the right side. The results of the second experiment were consistent with the first, and head motion trajectory analysis showed that participants had more movement toward the left side than the right side in the early parts of each trial. Conclusions: In this study, we suggested a new virtual reality (VR) evaluation technique and measured the human searching pattern in the FOR condition. We found a unique left-side attention bias in the FOR condition, and discussed implication of these results and potential attention bias factors. We believe this work is an important foundation for interactive 3D UI design, and we hope it will help people who have FOR handicaps.